"Nascent" Cu(0) nanoparticles‐mediated single electron transfer living radical polymerization of acrylonitrile at ambient temperature. Issue 6 (8th January 2013) - Yu, Yun‐Hai; Liu, Xiao‐Hui; Jia, Di; Cheng, Bo‐Wen; Zhang, Fei‐Jun; Li, Hui‐Na; Chen, Peng; Xie, Shan
Abstract Zn(0)/ppm concentrations of CuBr2 from 10 to 50 ppm was firstly used to catalyze radical polymerization of acrylonitrile at ambient temperature. The polymerization displayed typical living radical polymerization (LRP) characteristics, as evidenced by pseudo first‐order kinetics of polymerization, linear increase of number‐average molecular weight, and low polydispersity index (PDI) value. Effects of solvent, copper concentration, and initiator concentration on the polymerization reaction and molecular weight as well as PDI were investigated in detail. EC excelled NMP, DMF, and DMSO in terms of rate of polymerization as well as control of molecular weight and PDI. The increase of the copper concentration from 2.5 to 50 ppm leads to a higher rate of polymerization and a better control over the polymerization reaction. 1H NMR and GPC analyses as well as chain extension reaction confirmed the very high chain‐end functionality of the resultant polymer. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013